Elio Lugaresi (1926-2015): A founding father of the history of sleep disorders - de Santo, Rosa Maria (DELTOS, 2025)
The history of sleep disorder research began with the landmark 1953 paper by Aserinsky and Kleitman in Science, titled “Regularly Occurring Periods of Eye Motility and Concomitant Phenomena”. This field advanced on the shoulders of many giants, including Nathaniel Kleitman (Chicago), William C. Dement (Stanford), Henri Gastaut (Marseille), Elio Lugaresi (Bologna), Christian Guilleminault (Stanford), and Colin Sullivan (Sydney). Elio Lugaresi (Castiglione di Cervia, July 1, 1926 – Bologna, December 22, 2015) was one of those giants who transformed Sleep Medicine into one of the most dynamic fields of research and treatment. Lugaresi graduated from the University of Bologna in 1952. During his residency in Neurology at the same university, he trained in polysomnography (PSG) with Henri Gastaut from 1956 to 1957 in Marseille. He connected clinical observations with PSG data, and, upon returning to Bologna, began working with Giorgio Coccagna and others to conduct PSG recordings using a rudimentary electroencephalograph. The group produced seminal papers on (i) pulmonary pressures, arterial pressure, blood gases, breathing, and sleep; (ii) Restless legs syndrome and myoclonus; (iii) snoring and hypertension, which led to the identification of sleep apnoea as a risk factor for cardiovascular disease; and (iv) Fatal Familial Insomnia. In 1967, they organised the First International Congress on Sleep Medicine in Bologna. As stated in an interview with the Italian Association of Sleep Medicine, Lugaresi was inspired by the Renaissance idea that all knowledge should stem from the observation of humanity. Even in his emeritus days, he worked successfully, producing more than 500 papers and chapters, which have garnered him a long list of awards and honours. William C. Dement, referring to the originality of Lugaresi’s work, argued, “It is not clear what would have happened if an Italian neurologist, Elio Lugaresi, had not become very interested in obstructive sleep apnoea”.